State-of-the-art strategies for targeting the DNA damage response in cancer - Pilié, Patrick G. (Nat Rev Clin Oncol, 2019)
Genomic instability is a key hallmark of cancer that arises owing to defects in the DNA damage response (DDR) and/or increased replication stress. These alterations promote the clonal evolution of cancer cells via the accumulation of driver aberrations, including gene copy-number changes, rearrangements and mutations; however, these same defects also create vulnerabilities that are relatively specific to cancer cells, which could potentially be exploited to increase the therapeutic index of anticancer treatments and thereby improve patient outcomes. The discovery that BRCA-mutant cancer cells are exquisitely sensitive to inhibition of poly(ADP-ribose) polymerase has ushered in a new era of research on biomarker-driven synthetic lethal treatment strategies for different cancers. The therapeutic landscape of antitumour agents targeting the DDR has rapidly expanded to include inhibitors of other key mediators of DNA repair and replication, such as ATM, ATR, CHK1 and CHK2, DNA-PK and WEE1. Efforts to optimize these therapies are ongoing across a range of cancers, involving the development of predictive biomarker assays of responsiveness (beyond BRCA mutations), assessment of the mechanisms underlying intrinsic and acquired resistance, and evaluation of rational, tolerable combinations with standard-of-care treatments (such as chemotherapeutics and radiation), novel molecularly targeted agents and immune-checkpoint inhibitors. In this Review, we discuss the current status of anticancer therapies targeting the DDR.